SPORTS TOURISM BEHAVIOR OF TOURISTS IN SPORTS CITY CHON BURI - Panpayak, Amornrat; Singkram, Patantiya (Academic Journal of Thailand National Sports University, 2022)
The purposes of this study were 1) to study body of knowledge about sports tourism behaviors of tourists in sports city, Chon Buri; 2) to study sports tourism behaviors of tourists in sports city, Chon Buri; and 3) to compare sports tourism behaviors of tourists in sports city, Chon Buri, classified by individual factors. The study was a mix of qualitative research and quantitative research. A sample was selected from Thai tourists in sports city, Chon Buri, by using the infinite population sampling formula of Cochran. The calculated sample size from the formula was 384, so 400 samples were used by convenience sampling to avoid the error. The instrument was a questionnaire consisting of check list, rating scale, and open-ended question. The Index of Item - Objective Congruence (IOC) of the questionnaire was at 1.00 and the reliability of the questionnaire was at 0.94. Content analysis was used for the qualitative data. The quantitative data were analyzed by mean, standard deviation, percentage, t - test and F - test. The findings revealed that 1) body of knowledge about sports tourism behaviors consisted of 7 aspects namely sports tourism target, readiness for sports tourism, selecting sports tourism activities, sports tourism needs, decision for sports tourism, sports tourism plan making, and feeling about the country situation in sports tourist attractions; 2) sports tourism behaviors of tourists in sports city, Chon Buri, were at a high level with an arithmetic average at 3.94 in an overview of all aspects; and 3) comparison of sports tourism behaviors of tourists in sports city, Chon Buri, classified by individual factors indicated that the statistically significant difference of sports tourism behaviors was found in different genders at 0.05 level.